North African oil and foreign investment in changing market conditions - Bassam Fattouh (The Oxford Institute for Energy Studies, 2008)
The oil sectors in the North African countries of Algeria, Libya, Egypt and Sudan have witnessed major transformations in the past decade or so. In Algeria, government reforms in the mid 1980s resulted in the entry of a wide range foreign oil companies to an oil sector previously dominated by the state-owned oil company. In Libya, the lift of US sanctions and the opening of the oil sector to foreign investment through a series of licensing rounds created a new dynamism not seen since the mid 1950s when the country's oil industry kicked off. Egypt's oil policy of building partnerships with foreign oil companies makes it one of the most attractive countries for foreign investment despite its mature oilfields. In Sudan, Asian national oil companies transformed the prospects of the country's oil sector. Since 1999, Sudan's oil production has been rising steadily enabling the country to join the club of oil exporters.
Keywords: 330; Auslandsinvestition; Mineralölwirtschaft; Internationales Investitionsrecht; Algerien; Libyen; Ägypten; Sudan